THE DIALECTICS OF MA'RUF AMIN POLITICAL COMMUNICATION IN 2019 PRESIDENTIAL ELECTIONS: INFLUENCE ON VOTING PERSPECTIVE - Moh. Bashori Alwi Almanduri; Andi Faisal Bakti (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2022)
This article is a critical review of the phenomenon of political contestation in the 2019 presidential election. Partai Demokrasi Indonesia Perjuangan (PDI P) views the reality that NU is a political attribute of Ma’ruf Amin, as a tool to influence voting. In this context, the political strategy deliberately framed by the Prabowo camp aims to neutralize religious issues. Using a phenomenological approach and descriptive-analytical method, this research will dialogue with two specific problems, specifically: what is the role of Ma’ruf Amin as a voter for PDI P, and what is the role of voters in PDI P's victory? Furthermore, data were obtained through interviews, observations, and literature studies from several sources relevant to the research topic. The research results show that the Ma’ruf Amin entity as Jokowi's representative is seen as an absolute in gaining votes for the PDI P. Muslims as voters are divided into two types. First, the voters are dominated by reactive voters with lower secondary education levels. Second, the rational, responsive and active voters with an upper secondary education level.